Green and facile synthesis of few-layer graphene via liquid exfoliation process for Lithium-ion batteries - Lin, Pin-Chun; Wu, Jhao-Yi; Liu, Wei-Ren (Scientific reports, 2018)
A green and facile method using jet cavitation (JC) was utilized to prepare few layer graphene (FLG) derived from artificial graphite delamination without adding any strong acids and oxidants. The JC method not only provides high quality FLG with high yield but also demonstrate excellent electrochemical performance as anode materials for Li-ion batteries. Raman spectroscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) as well as BET isotherms and XPS are carried out in this study. The results of atomic force microscopy (AFM) further revealed that up to 85% of the prepared FLG were less than 10 layers. This exfoliation process happened mainly due to the cavitation-induced intensive tensile stress acting on the layered materials. Electrochemical measurements demonstrate that graphite anode delivered only 240 mAh/g while FLG anode achieved more than 322 mAh/g at 5C rate test. These results indicate that JC method not only paves the way for cheaper and safer production of graphene but also holds great potential applications in energy-related technology.